Transcription dynamics of heat shock proteins in response to thermal acclimation in Ostrinia furnacalis - Quan, Yudong; Wang, Zhenying; Wei, Hongyi; He, Kanglai (Frontiers in Physiology, 2022)
Acclimation to abiotic stress plays a critical role in insect adaption and evolution, particularly during extreme climate events. Heat shock proteins (HSPs) are evolutionarily conserved molecular chaperones caused by abiotic and biotic stressors. Understanding the relationship between thermal acclimation and the expression of specific HSPs is essential for addressing the functions of HSP families. This study investigated this issue using the Asian corn borer Ostrinia furnacalis, one of the most important corn pests in China. The transcription of HSP genes was induced in larvae exposed to 33°C. Thereafter, the larvae were exposed to 43°C, for 2 h, and then allowed to recover at 27 C for 0, 0.5, 1, 2, 4, 6, and 8 h. At the recovery times 0.5–4 h, most population tolerates less around 1–3 h than without recovery (at 0 h) suffering continuous heat stress (43 C). There is no difference in the heat tolerance at 6 h recovery, with similar transcriptional levels of HSPs as the control. However, a significant thermal tolerance was observed after 8 h of the recovery time, with a higher level of HSP70. In addition, the transcription of HSP60 and HSC70 (heat shock cognate protein 70) genes did not show a significant effect. HSP70 or HSP90 significantly upregulated within 1–2 h sustained heat stress (43 C) but declined at 6 h. Our findings revealed extreme thermal stress induced quick onset of HSP70 or HSP90 transcription. It could be interpreted as an adaptation to the drastic and rapid temperature variation. The thermal tolerance of larvae is significantly enhanced after 6 h of recovery and possibly regulated by HSP70.